Հայոց Եկեղեցու քրիստոսաբանութիւնը Ե. դարում. մարդացած Աստուած - Սահակեան, Տ. Մովսէս Քհնյ (Դաւիթ) (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Настоящая статья посвящена исследованию христологической мысли Армянской Церкви V века с особым акцентом на осмысление единства божественной и человеческой природ в Иисусе Христе в трудах армянских церковных отцов. Автор проводит всесторонний анализ широкого круга первоисточников, включая труды таких выдающихся армянских богословов, как Григорий Просветитель, Саак Партев, Месроп Маштоц, Езник Кохбаци, Павстос Бузанд, Егише, Мамбрэ Толкователь, Анания Переводчик, Иоанн Мандакуни, Агафангел, Мовсес Хоренаци и Лазарь Парпеци. Особое внимание уделяется тому, как Армянская Церковь сформировала уникальное христологическое учение, основанное на специфической терминологии, отражающей её самобытную богословскую традицию. В статье рассма триваются ключевые концепции, такие как «облачение» и «смешение», которые в армянском богословском дискурсе выражают совершенное и нераздельное единство божественного и человеческого во Христе. Статья детально раскрывает основные аспекты богословской мысли Армянской Церкви V века, подчёркивая глубину её христологических представлений, незыблемость догматической ортодоксии и её вклад в развитие христианской богословской традиции. This study investigates the development of Christological thought within the Armenian Church during the 5th century, with a particular emphasis on the theological articulation of the unity of divine and human natures in Jesus Christ as expounded by Armenian Church Fathers. The research undertakes a systematic analysis of an extensive corpus of primary sources, encompassing the works of eminent Armenian theologians such as Gregory the Illuminator, Sahak Parthev, Mesrop Mashtots, Eznik of Kolb, Faustus of Byzantium, Eghishe, Mambré the Interpreter, Anania the Translator, John Mandakuni, Agathangelos, Moses of Khoren, and Lazarus of Parpi. Special attention is accorded to the distinctive Christological paradigm formulated within the Armenian ecclesiastical tradition, which is predicated upon a conceptual framework reflecting its unique theological discourse. The study examines fundamental doctrinal constructs such as “clothing” and “mixing,” which, in the Armenian theological lexicon, encapsulate the ontological and soteriological dimensions of the perfect and indivisible hypostatic union of the divine and human natures in Christ. By offering a critical examination of the principal trajectories of Armenian theological thought in the 5th century, this study underscores the doctrinal profundity of its Christological formulations, the theological coherence and resilience of its dogmatic orthodoxy, and its enduring contribution to the broader landscape of patristic Christological discourse.
Keywords: Աստուածաբանութիւն; Քրիստոսաբանութիւն